Preliminary Analysis of the Effectiveness of Handing Criminal Acts by Children Under the Age - Antonio Daniguelo (Journal La Sociale, 2021)
The issue of drug addiction and illegal trafficking continues to plague nations across the globe. Between 153 and 300 million individuals, or 3.4 to 6.6 percent of the world's drug abusers aged 15 to 64 years, having used drugs at least once a year, with almost 12% (15.5 to 38.6 million people) of users being heavy addicts. Initially created for medicinal reasons (therapy), opioids became a political target for those seeking profit by introducing harmful addictive chemicals. Addition of hazardous addictive drugs may precipitate a person's hallucinations and addictions, wreaking havoc on the neurological system and organs of the body and ultimately resulting in death. The risks of drug addiction have prompted many nations to implement laws aimed at protecting citizens and prohibiting drug trafficking. This restriction eventually spawned illegal commerce and the growth of global marketplaces